MANAJEMEN SEKOLAH RAMAH ANAK PADA SEKOLAH BERBASIS KEAGAMAAN - Sadilla Salma Nabila; Burhanuddin Burhanuddin; Imron Arifin; Sadilla Salma Nabila; Burhanuddin Burhanuddin (Universitas Negeri Malang, 2024)
Abstract: This study aims to describe child-friendly school management where the main focus is fulfilling student's rights as a learner and individual. This study used a qualitative approach with a case study design. This research was conducted at Insan Amanah Primary School Malang. Collecting research data using interview, observation, and study documentation techniques. Analysis of research data started from data collection, data reduction, data presentation, and data verification. The result of this study are: (1) the background of the child-friendly school implementation at Insan Amanah Primary School Malang, (2) the process of planning, organizing, implementing, and evaluating child-friendly school at Insan Amanah Primary School Malang, (3) obstacles in child-friendly school management at Insan Amanah Primary School Malang, (4) school efforts in overcoming child-friendly school management constraints at Insan Amanah Primary School Malang, (5) parents' responses to child-friendly school management and its impact on the quality of children's education at Insan Amanah Primary School Malang.